Analysis of financial ratios on firm value: Testing dividend policy as moderation - Sartika, Lili; Malini, Helma; Azazi, Anwar; Mustika, Uray Ndaru (Institute of Computer Science (IOCS), 2025)
The purpose is to investigate the influence of profitability, solvency, and liquidity upon firm value and moderation of dividend policy from the IDX Kompas100 Index, with an analysis duration from 2020-2023 with a total of 122 observations. A purposive sampling approach is applied in this analysis, with criteria for firms that live consistently on the Kompas100 index, distribute dividends within analysis time, have profitable revenue, and are capable of meeting long-term and short-term debts. This research employs MRA with SPSS software. The outcome shows that profitability and liquidity have a positive result on firm value. Meanwhile, solvency shows an adverse influence on firm value. Additionally, dividend policy is able to moderate and intensify the outcome of solvency upon the firm value and weaken liquidity impact upon firm value, but it shows no sign of moderating effect on profitability upon firm value.